2002
DOI: 10.1046/j.1439-0434.2002.00709.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Performance of Asymptomatic and Yellow Leaf Syndrome‐affected Sugarcanes in Venezuela

Abstract: Serological analyses revealed the presence of the sugarcane yellow leaf virus (ScYLV) in asymptomatic (S–) and symptomatic (S+) yellow leaf syndrome‐affected sugarcane plants of the cultivars PR.692176, C.323–68, V.64–10, V.71–47, V.75–6, SP.72–2086, SP.72–1210, SP.74–2005, C.323–68, B.80–549 and B.82–363. Tests for the presence of the sugarcane yellows phytoplasma, carried out by Dr P. Jones (IACR‐Rothamsted), gave negative results in all cultivars. Physiological analyses were performed in the top visible dew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Growth reduction was also reported to occur without visible yellowing symptoms Lehrer et al 2009). Plants of cultivars with yellowing symptoms were reported to show an increase in the sucrose content of their leaves (Izaguirre-Mayoral et al 2002;Lehrer and Komor 2008), which was interpreted as the inhibition of assimilate translocation due to the disruption of phloem integrity.…”
Section: Sugarcane Yellow Leaf Virus (Scylv) Is a Polerovirusmentioning
confidence: 99%
“…Growth reduction was also reported to occur without visible yellowing symptoms Lehrer et al 2009). Plants of cultivars with yellowing symptoms were reported to show an increase in the sucrose content of their leaves (Izaguirre-Mayoral et al 2002;Lehrer and Komor 2008), which was interpreted as the inhibition of assimilate translocation due to the disruption of phloem integrity.…”
Section: Sugarcane Yellow Leaf Virus (Scylv) Is a Polerovirusmentioning
confidence: 99%
“…Sometimes pinkish-red discolouration on the adaxial surface of the midrib is also present. However, it has been also reported that a part of these symptoms could be related to other biotic or abiotic factors [4,5]. The disease infection results in reduction in sucrose content in stalks, and accumulation of sucrose in leaf midribs and therefore yield losses.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, 0.27-8.96 9 10 6 copy number of SCYLV population was detected in SCYLV-infected asymptomatic plants using RT-qPCR [4]. Izaguirre-Mayoral et al [8] rarely observed symptoms in all cultivars locally grown in Venezuela before or during the first ratoon, these becoming evident after the second ratoon. Also, they found about 25 % of the plants within a plot were asymptomatic.…”
Section: Discussionmentioning
confidence: 99%